Pengaruh Penyuluhan pada Remaja Putri tentang Pentingnya Merawat Personal Hygiene pada Kejadian Keputihan - Ratna Sari Dewi; Dovi Dwi Mardiyah Ningsih (Jurnal Kebidanan, 2022)
Personal hygiene is a practice of maintaining cleanliness physical, and psychological health, low personal hygiene care is a difficult situation to maintain cleanliness. Purpose of study was to determine the effect of counseling on adolescent girls about the importance of taking care personal hygiene in the incidence of vaginal discharge. The research method cross-sectional design with one group pre-and post-test. The population is 37 students aged 18-20 from class X, XI, and XII at SMKN 1 Jombang. Sampling purposive sampling to select a sample of 35 respondents. The independent variable is counseling to adolescents about the importance of taking care of personal hygiene, the dependent variable is the incidence of vaginal discharge, data analysis using T-Test, processing by editing, coding, scoring, and tabulating. The results of study before receiving personal hygiene counseling, more than 19 (59.4%) of 32 respondents reported experiencing vaginal discharge, and 7 of 32 respondents (21.9%) after receiving counseling reported experiencing vaginal discharge. The results T-Test statistic test (row) = 0.000 < (0.05), so that H1 is accepted and H0 is rejected, indicating that there is an effect of counseling on adolescent girls about the importance of taking care personal hygiene in the incidence of vaginal discharge at SMKN 1 Jombang. The conclusion is there is an effect of counseling on adolescent girls about the importance of taking care of personal hygiene in the occurrence of vaginal discharge, parents and teachers must be actively involved in educating adolescents about personal hygiene, reproductive health, especially vaginal discharge.